Bloodstream infections and antimicrobial sensitivity patterns in a tertiary care hospital of India. (October 2016) - Vasudeva, Nikita; Nirwan, Prem Singh; Shrivastava, Preeti
Background: Invasion of the bloodstream by microorganisms constitutes one of the most serious situations in infectious disease. Microorganisms present in circulating blood whether continuously, intermittently, or transiently are a threat to every organ in the body. Prevalence and antimicrobial susceptibility of microorganisms vary depending upon the geography and the use of antibiotics. Methods: A cross-sectional study to determine the prevalent organisms causing bloodstream infection was conducted. BACTEC BD 9050 system was used to identify the causative organism, and sub-cultures were done on MacConkey Agar and Blood Agar. Antibiotic susceptibility test (AST) was done using Kirby B Disk diffusion method. Results: A total of 170 patients were enrolled, and blood samples of 53 patients showed growth of organisms. Staphylococcus aureus was the most commonly isolated organism. Most of the Gram-positive cocci (GPC) were susceptible to vancomycin and linezolid. Most of the Gram-negative bacilli (GNB) showed sensitivity to cefoperazone/sulbactam followed by imipenem.